Analysis of Hybrid System in the Photovoltaic and Photothermal Technology - Sutanto, Bayu; Munawwaroh, Dita Anies; Bono, Bono; Herlambang, Yusuf Dewantoro; Sumarno, F Gatot; Alfauzi, Abdul Syukur (Eksergi, 2023)
The utilisation and optimisation of solar energy have a vital role in reducing the global need for conventional fossil energy. Moreover, it is also clean and eco-environmentally energy resources. The photovoltaic-thermal (PV-T) hybrid system that combines photovoltaic and photothermal technology is an ideal solution for creating high-efficiency energy conversion devices. In addition, this system can be constructed to be small and compact with a higher economic value than the conventional technology from the previous solar energy harvesters. This paper will review the PV-T hybrid system and provide the thermodynamic analysis and the feasibility study.